Leaving the Space—Opening the Gap? Electoral Effects of Parties' and Voters' Repositioning - Bernhard Weßels (The Changing German Voter, 2022)
Examining the German case in the wider Western European context for the period 1996–2017, the chapter investigates the role of supply and demand factors for vote switching in general and switching to right-wing populist parties in particular. Combining survey data from the CSES with party data from the Manifesto Project, the chapter shows that the growing success of right-wing populist parties, in Germany just as in other Western European countries, was a response to programmatic moves of mainstream center-left and center-right parties to the left. In general, voters' movements between parties did not follow a symmetric pattern. Changes to parties further left came about as responses to increasing voter-party distances on the socio-economic dimension. In the more recent past, switches to parties further right and, in particular, right-wing populist parties like the German AfD became more frequent, and they were associated with increasing distances on the socio-cultural dimension.
Additional information: The open access publication of the edited volume "The Changing German Voter" was financially supported by the Leibniz Association's Open Access Publication Fund for Monographs, the University of Mannheim, and the DGfW.
Keywords: 320; repositioning; vote switching; political supply; representation gap; AfD; right-wing populism